Avaliação ecotoxicológica por Aliivibrio fischeri de amostras contaminadas com sulfato de gentamicina e norfloxacino brutas e tratadas - Raquel Sampaio Jacob (2014)
Large quantities of different classes of pharmaceuticals are consumed annually, worldwide. These chemicals, once excreted, both in its original form and as metabolites, very often remain stable after conventional or even advanced treatments. Aquatic ecotoxicology may be a science of great value to support in addressing the problems of contamination of bodies of water by toxic compounds such as pharmaceuticals. The aim of this study was to assess the ecotoxicological analysis by Aliivibrio fischeri of raw and treated synthetic effluents contaminated with norfloxacin and gentamicin sulfate. The treatments contemplated in the study were the biological one, UV radiation, H2O2, UV/ H2O2, homogeneous Fenton reaction and photo-Fenton. The raw effluent of norfloxacin at 15 mg/L is toxic, whereas hormesis was detected for the raw effluent of gentamicin sulfate at 100 mg/L. Amongst the tested types of biological treatment, the more efficient is the one that uses biomass from the UASB reactor, followed by the Anaerobic Digester and, lastly, Activated Sludge. Regarding the ecotoxicological tests, one can say that the UASB reactor and the Anaerobic Digester are sufficient to eliminate the toxicity of antibiotics, while the Activated Sludge process generates toxic effluents. The ecotoxicological analyses of samples treated with H202 state that there is not residual toxicity, although the removal efficiency of the pharmaceuticals is low. On the topic of UV treatment, it is efficient to degrade the pharmaceuticals, but only after long reaction time. Moreover, a complete mineralization of antibiotics does not happen and both samples are considered toxic. On the other hand, for the UV/H2O2 method, there were 100% removals of norfloxacin and 90% of gentamicin sulfate. However, due to the formation of harmful by-products of degradation, both samples have become toxic after such processing. The experiments optimized by homogeneous Fenton reaction provided medium degradation of 55% (TOC) and 59% (UV/VIS), for the norfloxacin samples; and 82% (TOC) for the gentamicin sulfate samples. The treatment was effective in eliminating toxicity from norfloxacin, but it generated a toxic effluent from gentamicin sulfate. With respect to the treatment optimized by photo-Fenton, although it is more efficient in the removal of pharmaceuticals than the Fenton treatment, it generates more toxic samples, especially in the case of gentamicin sulfate.